Comprehensive study on the stability and failure mechanism of landslides under rainfall and earthquake in northwest mountainous areas - Yang, Weixin; Zhang, Yonggang; Zhang, Lei; Bai, Gexue; Wan, Baofeng; An, Ning (Frontiers in Earth Science, 2024)
Landslides and geological disasters occur frequently in the mountainous areas of northwest China, seriously threatening people’s life and property of the region. In this study, we investigated the Lijie Beishan landslide as a typical case and combines the results of on-site geological surveys to conduct two-dimensional and three-dimensional numerical simulations of the landslide, evaluating its stability under self-weight, rainfall, and earthquake action. By analyzing the generalized shear strain, displacement, and stability coefficient of the landslide, it is determined that the stability of the landslide shows a decreasing trend under static, rainfall, and earthquake conditions. Landslides exhibit tension controlled failure modes under normal static and rainfall conditions, and translational failure modes under earthquake conditions. Compared with static and rainfall conditions, landslides have the largest volume and sliding distance under earthquake conditions. By combining the transfer coefficient method and the simplified Bishop method, a comparative analysis was conducted on the stability of the landslide. It was found that the stability coefficients under different working conditions were consistent with the simulation results, which verified the reliability of the simulation results. The research results of this paper will assist in clarifying the development mechanism of this type of landslides and provide valuable references for the stability evaluation of landslides in the northwest mountainous areas.